An expanded description, natural history, and genetic variation of the recently described cobra species Naja fuxi Shi et al., 2022 - Ratnarathorn N. (2023)
The morphological variation, extended distribution, and sequence divergence of a recently described of cobra Naja fuxi Shi et al., 2022 captured from mountainous areas in Thailand are evaluated by using molecular and morphological analyses. We investigated the genetic variation and affinities of 72 specimens in the genus Naja by using mitochondrial DNA (cytochrome b and control region) and the nuclear DNA gene, C-mos. Morphological examination was conducted for 33 cobra specimens obtained from the northern, western, and north-eastern regions, and data on their natural history were gathered during field surveys. A high degree of genetic differentiation was shown to exist between the cobras collected from lowlands and those from mountainous areas. N. fuxi occurs in uplands bordering Thailand's Central Basin, whereas the similar looking N. kaouthia Lesson, 1831 is more or less restricted to the lowlands. All phylogenetic and network analyses supported a distinct clade of N. fuxi from north, west, and, north-east regions. In addition, N. fuxi seems to exhibit a split between the north-eastern population and those from the north and west. The range of N. fuxi probably extends far into the mountainous areas of the neighbouring countries Myanmar, Laos, and Vietnam. Morphologically, N. fuxi in Thailand can be distinguished from all other cobra species in the adjacent Oriental Region. The speciation of cobras in Thailand likely reflects key events in the region's geographical, climate and environmental history.